Magrib Mengaji Upaya Membangun Kebiasaan Membaca Alquran pada Anak di Kelurahan Tanjung Ibus Kecamatan Secanggang Kabupaten Langkat - Lewis Pramana Lubis; Annisa Azzahra; Nurul Della (Medan Resource Center, 2021)
Maghrib recite is a method used to instill the habit of reading the recite to children in Tanjung Ibus Village, Secanggang District, Langkat Regency, North Sumatra. The strategy of the Maghrib recite is to promote reciting activities in every hamlet, either through the mosque or through the homes of the recite teachers. In addition, the role of parents at home is also very important in this movement. If the child is reluctant to go to the mosque or the teacher's house, the child can recite the recite at home under the supervision of his parents. This activity is carried out after the sunset prayer. The Maghrib recite movement is an effort to familiarize children with reading the recite, which will later form the Qur'anic generation. In addition, restoring the traditions and culture of Muslims has long existed, but along with the times, this good tradition has begun to be abandoned.